The Influence of Sucrose and Amonium Sulphate Concentration on Quality of Nata Gracillaria sp. - Sri Purwaningsih; Ella Salamah; Apit Setiani (Jurnal Pengolahan Hasil Perikanan Indonesia, 2007)
Nata is biomass that mostly consist of cellulose, physically resemble to agar with white layer.In this research nata was made from seaweed that is Gracillaria sp. as a raw material, because of thecheap price of this seaweed and it content of high fiber. The objective of this research was toinvestigate the possibility of Gracillaria used as nata raw material and to learn influence of sucroseand ammonium sulphate concentration on quality of nata. Result indicated that the ratio of seaweedand water generated the highest yield was 1:70 (w/v). The combination of sucrose and ammoniumsulphate concentration significantly influenced to yield, thickness, degree of whiteness, crude fiber,dietary fiber of nata. Using sucrose was 7.5 %(w/v) and ammonium sulphate was 0.75 % producednata with the best characterization.Key words: Gracillaria sp., nata